PROMOSI KESEHATAN TENTANG “BEYOUTIFUL: (DROP THE DOUBTS, BE THE REAL YOU) DI SMK PASUNDAN JATINANGOR KECAMATAN SUMEDANG - Iwan Shalahuddin; Udin Rosidin; Efri Widianti (Universitas Mataram, 2026)
Adolescents are a vulnerable age group prone to negative body image issues due to social media exposure, peer pressure, and unrealistic beauty standards. The health education and promotion program entitled “BEYOUTIFUL: Drop the Doubts, Be the Real You!” was implemented at SMKS Pasundan Jatinangor to improve students' understanding of self-love, positive body image, and self-acceptance. The program applied experiential learning, Social Learning Theory (SLT), Health Belief Model (HBM), and humanistic learning theories. Evaluation was conducted through pre- and post-tests, reflective discussions, and observation of student engagement. Results showed a significant increase in students’ knowledge of mental health and self-love, along with a more positive attitude towards themselves. The program also created a safe space for students to express themselves and build peer support. It is recommended that mental health education be integrated into the school curriculum and peer support groups be established as a sustainable effort to promote mentally and emotionally healthy adolescents